2015
DOI: 10.1007/s13369-015-1727-5
|View full text |Cite
|
Sign up to set email alerts
|

Aerogel-Assisted Support Pillars for Thermal Performance Enhancement of Vacuum Glazing: A CFD Research for a Commercial Product

Abstract: Vacuum glazing is an up-and-coming and rapidly developing technology which has a great potential to reduce heating and cooling demand of buildings in winter and summer, respectively. In this paper, the world's first commercially available vacuum glazing product is numerically investigated through a CFD-based research. Accuracy of the CFD model is compared with the manufacturer's thermal performance report, and an excellent agreement is observed. Then, translucent aerogel support pillars are recommended for com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Windows are the main units of the building envelope for the ventilation of buildings, solar energy gain, and easy visibility from outside [22]- [24]. On the other hand, what kind of role they play in the total energy consumption in buildings is uncertain.…”
Section: Production Of Solar Glass Panelmentioning
confidence: 99%
“…Windows are the main units of the building envelope for the ventilation of buildings, solar energy gain, and easy visibility from outside [22]- [24]. On the other hand, what kind of role they play in the total energy consumption in buildings is uncertain.…”
Section: Production Of Solar Glass Panelmentioning
confidence: 99%
“…As reported by Jelle et al [66], SPACIA-21 a product from the Pilkington Company (Tokyo, Japan) (Figure 9), shows excellent promise with an overall heat loss coefficient of 0.70 W/m 2 K and a small external thickness of 21 mm, as opposed to a comparable multilayer glazing configuration at 40 mm. Cuce and Riffat [67] included translucent aerogel support pillars into a vacuum glazing design and modelled their impact on thermal performance and found a 44% reduction in the panels U-value. The authors indicated that a lower U-value could be reached if the number and distribution of the support pillars is optimised.…”
Section: Glazing Layersmentioning
confidence: 99%
“…Further reports reveal that space cooling-related energy use shows 60% rise from 2000 to 2010, which corresponds to 4% of global energy consumption in 2010 [8]. Remarkable influence of buildings on heating and cooling demand can be easily ascribed to the insufficient thermal insulation performance of building elements such as external walls, windows, roofs and floors [9][10][11][12][13][14][15]. In this respect, intensive studies are carried out to improve the thermal insulation performance of the aforesaid building elements notably external walls in a renewable, low-cost and ecofriendly manner [16].…”
Section: Introductionmentioning
confidence: 99%